2013
DOI: 10.1002/etc.2245
|View full text |Cite
|
Sign up to set email alerts
|

The impact of endocrine‐disrupting chemicals on oxidative stress and innate immune response in zebrafish embryos

Abstract: Bisphenol A (BPA) and nonylphenol (NP) are well known endocrine-disrupting chemicals (EDCs) ubiquitous in the aquatic environment and are an ecotoxicological risk for the health of aquatic organisms. Limited attention has been given to the immunotoxicity of these chemicals. The present study revealed a concentration-dependent increase of reactive oxygen species content and an induced expression of redox-sensitive transcription factors in zebrafish embryos after exposure to various concentrations of BPA, NP, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
45
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 128 publications
(54 citation statements)
references
References 40 publications
7
45
2
Order By: Relevance
“…These observations reflect those of previous studies depicting the activation of classical nuclear Esrs as capable of strongly affecting fish leukocyte gene expression, not only through transcriptomal alteration, but also through the modulation of the proteome metabolism (Liarte et al, 2011c). While some works developed using human cells point to the ability of estrogenic compounds to enhance IFNs and TLRs expression despite the lack of estrogen responsive elements in their promoters (Lindner et al, 1997;Seillet et al, 2012), our data contrast with the little evidence existing about immune impairment after estrogenic EDC exposure in the zebrafish (Xu et al, 2013). Whatever the outcome, the drastic induction of socs1 in Esr2b mutant zebrafish would establish a faulty antiviral response in the early stages of the infection, enabling the virus to quickly replicate and disseminate, as demonstrated by the expression levels of its viral capsid protein.…”
Section: Discussioncontrasting
confidence: 85%
“…These observations reflect those of previous studies depicting the activation of classical nuclear Esrs as capable of strongly affecting fish leukocyte gene expression, not only through transcriptomal alteration, but also through the modulation of the proteome metabolism (Liarte et al, 2011c). While some works developed using human cells point to the ability of estrogenic compounds to enhance IFNs and TLRs expression despite the lack of estrogen responsive elements in their promoters (Lindner et al, 1997;Seillet et al, 2012), our data contrast with the little evidence existing about immune impairment after estrogenic EDC exposure in the zebrafish (Xu et al, 2013). Whatever the outcome, the drastic induction of socs1 in Esr2b mutant zebrafish would establish a faulty antiviral response in the early stages of the infection, enabling the virus to quickly replicate and disseminate, as demonstrated by the expression levels of its viral capsid protein.…”
Section: Discussioncontrasting
confidence: 85%
“…With increased BPA exposure, ROS and NO levels, iNOS and TNOS activities, as well as immune gene expression such as IL-1β, IL-10 in the macrophages was significantly induced in a concentration-dependent manner, consistent with our previous in vivo observations on zebrafish embryos upon 7 day BPA treatment. 21 Moreover, the alterations of most tested parameters were significantly correlated (SI Table S2), indicating a coordinated modulation process in macrophages responded to increased BPA exposure. Consistent with our observation on M17 (IL-6 like), Liu et al 25 have showed that BPA treatment increased pro-inflammatory cytokines IL-6 and tumor necrosis factor-α (TNF-α) production in THP1 macrophages and primary human macrophages at BPA concentrations of 0.01 and 0.1 μM, that is, about 2 and 20 μg/L.…”
Section: ■ Discussionmentioning
confidence: 97%
“…Exposure to several manmade chemicals, organic pollutants, endocrine disrupting chemicals like insecticides, pesticides, bisphenol A, phthalates not only disrupt the hypothalmopitutary gonadal axis but also induce oxidative stress. 31 A sedentary life style, fast foods, smoking, excess alcohol intake, electromagnetic radiation, high temperature all result in exposure to increased free radical levels. Thus free radicals can be produced by both exogenous and endogenous sources.…”
Section: Discussionmentioning
confidence: 99%